Sarcoidosis and lymphoma: case series and literature review: - Maayan, H.; Ashkenazi, Y.; Nagler, et al., A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
This is a case series and literature review of patients with various types of hematologic disorders and sarcoidosis. The patients were treated in the hematologic day care unit at Shaare Zedek medical center and at the hematology department of Chaim Sheba Medical Center hospital from 1990 until 2008.We report eight cases from two centers where both diseases were diagnosed at different time points.We have shown that there might be coincidence of two rare conditions and emphasize the importance of tissues sampling of lesions suspected to be a relapse of a former biopsy-proven disease, even in the presence of positive PET results.